Revitalisasi Peran Ayah dalam Keluarga: Tinjauan Tafsir Kementerian Agama terhadap Fenomena Fatherless di Indonesia - Khomairoh, Siti; Walkaromah, Naylul Izzah (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2024)
Indonesia is highlighted as the third-ranked "fatherless country." A fatherless country refers to a nation where the role and presence of fathers in childcare are minimal. The lack of paternal involvement in the upbringing and education of children is driven by deeply rooted societal stigmas. This phenomenon is rooted in a strong patriarchal culture, in which childcare is seen entirely as the mother’s responsibility. Based on the above, a solution is needed to respond to this phenomenon. The fatherless issue calls on society to re-evaluate the parameters of a father’s role in the family, especially toward children. The Qur’an, as a guide for Muslims, contains indicators and answers to all of life’s problems. Therefore, seeking solutions to the fatherless phenomenon through the Qur’an becomes crucial to implement. This research is qualitative in nature, using a library research approach. The data is presented using descriptive analytical techniques. The study finds that the fatherless phenomenon contradicts the substance of the Qur’an. The interpretation (Tafsir) by Indonesia’s Ministry of Religious Affairs (KEMENAG RI) contains numerous verses that imply exemplary behavior and ideal values a father should embody toward his child. The interpretation by the KEMENAG RI team of these verses is relevant for application in the Indonesian context. Based on the analysis, the involvement of fathers in the childcare process has a significant positive impact on the child's growth and development. By highlighting various examples of the ideal father figure from the KEMENAG RI Tafsir, it is hoped that these can be implemented to help reduce the percentage of fatherlessness in Indonesia.